2014
DOI: 10.15517/rbt.v62i2.8482
|View full text |Cite
|
Sign up to set email alerts
|

Estratificación vertical de briófitos epífitos encontrados en Quercus humboldtii (Fagaceae) de Boyacá, Colombia

Abstract: Vertical stratification of epiphytic bryophytes found on Quercus humboldtii (Fagaceae) from Boyacá, Colombia. Oak forest represents an ecologically important plant formation in Colombia, partly due to the large amount of epiphyte flora that harbors, especially non-vascular plants which have been poorly studied in Colombia. One of the biggest oak forests in the country is the one found in the Parque Natural Municipal "Robledales de Tipacoque" (PNMRT), in Boyacá, municipality of Tipacoque. The epiphyte bryoflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
3
0
6
Order By: Relevance
“…Different studies have indicated that organic matter accumulated on host could influence the stability of the substrate and, therefore, favor the establishment of epiphytes (Ingram & Nadkarni 1993, Tremblay et al 1998, Ruíz-Cordova et al 2014. The accumulation of organic substrate is larger in microenvironmental conditions with lesser availability of light and high level of humidity (Mota de Oliveira et al 2009, Gil-Novoa & Morales-Puentes 2014. This organic matter accumulated on the trunk and primary branches of the host can provide constant humidity, which is a restricting factor for epiphytic plants, particularly during the germination stages (Pypker et al 2006, Scheffknecht et al 2010, Mondragón et al 2015.…”
Section: Host Speciesmentioning
confidence: 99%
“…Different studies have indicated that organic matter accumulated on host could influence the stability of the substrate and, therefore, favor the establishment of epiphytes (Ingram & Nadkarni 1993, Tremblay et al 1998, Ruíz-Cordova et al 2014. The accumulation of organic substrate is larger in microenvironmental conditions with lesser availability of light and high level of humidity (Mota de Oliveira et al 2009, Gil-Novoa & Morales-Puentes 2014. This organic matter accumulated on the trunk and primary branches of the host can provide constant humidity, which is a restricting factor for epiphytic plants, particularly during the germination stages (Pypker et al 2006, Scheffknecht et al 2010, Mondragón et al 2015.…”
Section: Host Speciesmentioning
confidence: 99%
“…Por otra parte, dada la amplia heterogeneidad geográfica en la región, es probable que el número de especies continúe aumentando con la realización de futuros estudios, incluyendo áreas más alejadas de la población y en otras latitudes, con la exploración a nivel del suelo y de partes más altas de los árboles, como el dosel. En el último caso, esto permitiría incluir musgos que se distribuyen en este nivel (Sporn et al, 2010), que por diferentes microambientes a lo largo de los árboles hospederos, son distintos a los encontrados en estratos más bajos (Boch et al, 2013;Gil-Novoa y Morales-Puentes, 2014). Por lo anterior y por la extensión de este bosque, es probable que su riqueza sea superior a la estimada en este estudio.…”
Section: Discussionunclassified
“…De acuerdo con Woda, Huber y Dohrenbusch (2006), en árboles con características estructurales como una copa densa y un tronco cubierto por corteza dura y lisa que se fracciona en unas placas, afectan el crecimiento de plantas epifitas, esto a razón de la competencia por luz del dosel del árbol denso y las condiciones que evitan la adherencia de las raíces de la epifita. Por lo tanto, la distribución de las plantas epifitas depende para su supervivencia, de la textura del hospedero, la porosidad de la corteza del árbol, ph del medio donde se adhiere, cantidad de luz disponible y la humedad (Gil y Morales, 2014). Siendo los anteriores requisitos indispensables para un establecimiento satisfactorio de una planta epifita, donde revela que la facilidad para penetrar la corteza es necesaria, así como el ph del área del árbol adherido, lo cual revela el intercambio de sustancias entre ambos seres vivos, donde indiscutiblemente no hay solo una fijación con el árbol hospedero.…”
Section: Efecto Parásito De Las Orquídeas Sobre Las Plantas Hospederasunclassified